Dermatological manifestations in cardiofaciocutaneous syndrome: a prospective multicentric study of 45 mutation‐positive patients. (1st January 2019) - Bessis, D.; Morice‐Picard, F.; Bourrat, E.; Abadie, C.; Aouinti, S.; Baumann, C.; Best, M.; Bursztejn, A.‐C.; Capri, Y.; Chiaverini, C.; Coubes, C.; Giuliano, F.; et al.
Summary: Background: Data on dermatological manifestations of cardiofaciocutaneous syndrome (CFCS) remain heterogeneous and almost without expert dermatological classification. Objectives: To describe the dermatological manifestations of CFCS; to compare them with the literature findings; to assess those discriminating CFCS from other RASopathies, including Noonan syndrome (NS) and Costello syndrome (CS); and to test for dermatological phenotype–genotype correlations. Methods: We performed a 4‐year, large, prospective, multicentric, collaborative dermatological and genetic study. Results: Forty‐five patients were enrolled. Hair abnormalities were ubiquitous, including scarcity or absence of eyebrows and wavy or curly hair in 73% and 69% of patients, respectively. Keratosis pilaris (KP), ulerythema ophryogenes (UO), palmoplantar hyperkeratosis (PPHK) and multiple melanocytic naevi (MMN; over 50 naevi) were noted in 82%, 44%, 27% and 29% of patients, respectively. Scarcity or absence of eyebrows, association of UO and PPHK, diffuse KP and MMN best differentiated CFCS from NS and CS. Oral acitretin may be highly beneficial for therapeutic management of PPHK, whereas treatment of UO by topical sirolimus 1% failed. No significant dermatological phenotype–genotype correlation was determined. Conclusions: A thorough knowledge of CFCS skin manifestations would help in making a positive diagnosis and differentiating CFCS from CS and NS.